Delayed elimination communication is a crucial factor in disposable diaper dependence in Chinese preschool-aged children - Yu, Jia-ting; Mao, Qiu-fang; Ji, Feng-ping; Zhao, Ying; Hu, Hui-jie; Zhang, Yan-ping; Yang, Jing; Wang, Qing-wei; Lu, Wei; Wen, Jian Guo (Frontiers in Pediatrics, 2023)
Purpose Elimination communication (EC) is considered to be a milestone in a child's development. Nowadays, a trend toward an older age at EC initiation has been observed globally, probably due to the convenience of disposable diaper use in daily life. The study aimed to identify potential risk factors for disposable diaper dependence (DDD) and evaluate whether an early/proper EC can reduce the risk of DDD among children in China. Methods A cross-sectional study was performed on 13,500 children in mainland China from October 2019 to March 2020. An anonymous questionnaire was used to collect information including the sociodemographic characteristics, details about DDD and EC, and the effect of DDD on the quality of life of children. Data were analyzed by SPSS and R software. Results The overall prevalence of DDD was 4.17% (4.31% in boys; 4.02% in girls) and decreased with age, from 8.71% at 2 years to 0.73% at 6 years (χ2trend = 210.392, P < 0.001). In univariable analysis, age, location or EC were associated with DDD. Four independent factors—age, location (urban), caregivers with high education levels (junior college or above) and delayed EC (after 12 months of age)—were identified to be significantly associated with DDD risk in logistic regression model. Compared with EC onset after 12 months of age, EC onset before 12 months of age was associated with a 79.6% (model 2) reduction in DDD. Four independent factors were selected to establish the nomogram for DDD based on the results of logistic regression analysis. The C-index (0.770) and the AUC (>0.7) indicated satisfactory discriminative ability of the nomogram. The calibration diagrams showed favorable consistency between the prediction of the nomogram and actual observations. Conclusion Our findings indicate the joint contribution of age, location, caregivers’ education level and EC to DDD in Chinese preschool-aged children. Timely cessation of the use of disposable diapers and early/proper EC may help to reduce the risk of DDD in children.